Research trends on cancer neuroscience: a bibliometric and visualized analysis - Ma, Xinru; Deng, Kun; Sun, Yingnan; Wu, Minghua (Frontiers in Neuroscience, 2024)
BackgroundRecently, cancer neuroscience has become the focus for scientists. Interactions between the nervous system and cancer (both systemic and local) can regulate tumorigenesis, progression, treatment resistance, compromise of anti-cancer immunity, and provocation of tumor-promoting inflammation. We assessed the related research on cancer neuroscience through bibliometric analysis and explored the research status and hotspots from 2020 to 2024.MethodsPublications on cancer neuroscience retrieved from the Web of Science Core Collection. CiteSpace, VOSviewer, and Scimago Graphica were used to analyze and visualize the result.ResultsA total of 744 publications were retrieved, with an upward trend in the overall number of articles published over the last 5 years. As it has the highest number of publications (n = 242) and citations (average 13.63 citations per article), the United States holds an absolute voice in the field of cancer neuroscience. The most productive organizations and journals were Shanghai Jiaotong University (n = 24) and Cancers (n = 45), respectively. Monje M (H-index = 53), Hondermarck H (H-index = 42), and Amit M (H-index = 39) were the three researchers who have contributed most to the field. From a global perspective, research hotspots in cancer neuroscience comprise nerve/neuron-tumor cell interactions, crosstalk between the nervous system and other components of the tumor microenvironment (such as immune cells), as well as the impact of tumors and tumor therapies on nervous system function.ConclusionThe United States and European countries are dominating the field of cancer neuroscience, while developing countries such as China are growing rapidly but with limited impact. The next focal point in this field is likely to be neurotrophic factors. Cancer neuroscience is still in its infancy, which means that many of the interactions and mechanisms between the nervous system and cancer are not yet fully understood. Further investigation is necessary to probe the interactions of the nervous system with cancer cell subpopulations and other components of the tumor microenvironment.